(untitled) (Revista Educação, Artes e Inclusão, 2025)
This study is based on an understanding of Art as knowledge and creation, considering it as a form of expression and manifestation of historically produced culture. To this end, the object of this analysis was the study of the teaching of Art in the training of teacher-pedagogues, based on two Pedagogy courses in the state of Tocantins, one in a private institution and the other in a public one. The research problem lies in analysing the training perspective present in the curriculum of these Pedagogy courses and whether it prioritises the humanising training of the teacher-pedagogue. The aim of the research was to reflect on the hegemonic pedagogical trends present in the teacher-pedagogue training curriculum. In the course of this research, by adopting the method of historical-dialectical materialism for the bibliographical and documentary research, the socio-political and educational approaches were combined with an analysis of the teaching of art in the aforementioned courses. The research found that the courses prioritise technical training for the development of ‘skills and competences’, based on the idea of the ‘learning to learn’ pedagogy that has become hegemonic in national education. The adaptive and conformative perspective has influenced the very conception of what a pedagogy course is and, by extension, interferes in the specific field of art education.